Defence planning and alliances: Portugal in the early years of the cold war (1945-59) - Rocha, J. S. (Portuguese Journal of Social Science, 2018)
This article looks at how Portuguese defence planning was executed in the years 1945–59, and seeks to assess to what extent this same planning was subject to constraints derived from the alliances established by the Portuguese government. During this period, Portugal was faced with internal and external issues of difficult resolution. Internationally, its interests and its obligations were focused on the Atlantic powers, the ones who had the necessary means and organization to counter the Soviet threat. At home, the Portuguese authorities considered that Portugal was first of all part of the Iberian peninsula and, as such, made common cause for its military defence with its turbulent and, at that time, less respectable Spanish neighbour.